2018
DOI: 10.3390/sym10080353
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis on SDDO-Based BM123-64 Designs Suitable for Various IoT Application Targets

Abstract: BM123-64 block cipher, which was proposed by Minh, N.H. and Bac, D.T. in 2014, was designed for high speed communication applications factors. It was constructed in hybrid controlled substitution–permutation network (CSPN) models with two types of basic controlled elements (CE) in distinctive designs. This cipher is based on switchable data-dependent operations (SDDO) and covers dependent-operations suitable for efficient primitive approaches for cipher constructions that can generate key schedule in a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, we require 2 4 − 1 variables in the cube for an attack against the 5-round Sycon. In the same way, after six rounds, the degree of S is 2 5 . Thus, we need 2 5 − 1 variables in the cube.…”
Section: Idea and Scenariomentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, we require 2 4 − 1 variables in the cube for an attack against the 5-round Sycon. In the same way, after six rounds, the degree of S is 2 5 . Thus, we need 2 5 − 1 variables in the cube.…”
Section: Idea and Scenariomentioning
confidence: 98%
“…However, the importance of information security must be emphasized, because there are risks of being exposed to cyber security threat, manipulation or leakage of data and invasion of privacy during the transmission of data by wireless communication [1][2][3]. In wireless communication, information security may be provided through cryptographic algorithms [4,5]. However, since the security strength of cryptographic algorithms does not provide immutability, it must be continuously re-evaluated and reviewed for proper use.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the attack had become effective cryptanalysis technique applying for various cipher mechanisms since the target aims to exploit two distinctive related-key differential characteristics for finding right quartets with high probability. Some of the previous cryptanalysis that used this attack scenario on DDO-based ciphers had given high efficiency and high probability in cryptanalytic results, like on BMD-128 [9], XO-64 [10], DDO-64 [11], MD-64 [12], and BM123-64 [3]. In the model of related-key boomerang attack, the cipher E is divided into two sub-ciphers, depicted as E = E 1 ○E 0 .…”
Section: Related Studymentioning
confidence: 99%
“…Symmetry-Adapted Machine Learning for Information Security delivers successfully accepted submissions [1][2][3][4][5][6][7][8][9][10][11][12] in this Special Issue of Symmetry. Proposals for several innovative paradigms, novel architectural designs, and frameworks with symmetry-adapted machine learning are covered in this particular issue.…”
Section: Symmetry-adapted Machine Learning For Information Securitymentioning
confidence: 99%
“…Phuc et al [1] propose a new attack method for the BM123-64 structure based on related-key attacks. The study addresses the security weaknesses found in ciphers based on data-dependent operations implemented in lightweight targets and rapid transformation.…”
Section: Symmetry-adapted Machine Learning For Information Securitymentioning
confidence: 99%